2006
DOI: 10.1124/jpet.106.106286
|View full text |Cite
|
Sign up to set email alerts
|

Iptakalim Modulates ATP-Sensitive K+ Channels in Dopamine Neurons from Rat Substantia Nigra Pars Compacta

Abstract: Iptakalim, a novel cardiovascular ATP-sensitive K ϩ (K ATP ) channel opener, exerts neuroprotective effects on dopaminergic (DA) neurons against metabolic stress-induced neurotoxicity, but the mechanisms are largely unknown. Here, we examined the effects of iptakalim on functional K ATP channels in the plasma membrane (pm) and mitochondrial membrane using patch-clamp and fluorescence-imaging techniques. In identified DA neurons acutely dissociated from rat substantia nigra pars compacta (SNc), both the mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
(47 reference statements)
1
18
1
Order By: Relevance
“…Doses up to 500 mmol/l have been reported to inhibit selectively mitoK(ATP) channels without affecting surface K(ATP) currents (Sato et al 2000;Hu et al 1999). However, we did not observe significant differences between the effect of 10 μM 5-HD and 100 μM 5-HD, and high doses of 5-HD may have nonspecific side effects independent of any action on mitoK(ATP), as reported for mitoK(ATP) openers, which have been observed to act as channel closers at high concentrations (Garlid 2000;Wu et al 2006). In the present study, we therefore used the lowest dose of 5-HD (10 μM), which proved effective at inhibiting the effects of angiotensin II.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…Doses up to 500 mmol/l have been reported to inhibit selectively mitoK(ATP) channels without affecting surface K(ATP) currents (Sato et al 2000;Hu et al 1999). However, we did not observe significant differences between the effect of 10 μM 5-HD and 100 μM 5-HD, and high doses of 5-HD may have nonspecific side effects independent of any action on mitoK(ATP), as reported for mitoK(ATP) openers, which have been observed to act as channel closers at high concentrations (Garlid 2000;Wu et al 2006). In the present study, we therefore used the lowest dose of 5-HD (10 μM), which proved effective at inhibiting the effects of angiotensin II.…”
Section: Discussioncontrasting
confidence: 41%
“…The discrepancies may be related to different experimental conditions. MitoK(ATP) openers have been reported to act as channel closers at high concentrations (Wu et al 2006). It has also been suggested that opening of mitoK(ATP) may have two distinct consequences, depending on the underlying bioenergetic state (Garlid et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Doses up to 500 mmol/L have been observed to selectively inhibit mitoKATP channels without affecting surface KATP currents (Sato et al, 1998(Sato et al, , 2000Hu et al, 1999), although 5-HD is a specific blocker of the mito-KATP channels at lower doses such as 10 mM (McCullough et al, 1991;Garlid et al, 1997;Kimura et al, 2005b;Zhang et al, 2007: Costa andGarlid, 2008). In the present study, therefore, we used the lowest dose of 5-HD (10 mM), previously found to block mitoKATP channels in DAergic neurons (Wu et al, 2006;RodriguezPallares et al, 2009), to prevent any potential nonspecific side effects of high doses of 5-HD. Furthermore, the results obtained with 5-HD were confirmed with glibenclamide, which acts as a general inhibitor of KATP channels.…”
Section: Discussionmentioning
confidence: 94%
“…Mitochondrial K ATP (Mito-K ATP ) channels play the roles in controlling the mitochondrial volume, regulating the translation of metabolic status of cells, and responsing open/ close channels to injury for neurodegeneration. It is hypothesized that preconditioning of K ATP channels may render neuronal tissues resistant to neurodegenerative process [15] . To test this hypothesis , Tai and Truong et al found that, at the cellular level, activation of K ATP channels in PC12 cells confered protection against mitochondrial complex-I inhibition-induced cell death by rotenone which had been proven to be the pathogenesis of PD [16] .…”
Section: Roles Of K Atp Channels In Pdmentioning
confidence: 99%